Maxillofacial Injuries in Cyclists: A Biomechanical Approach for the Analysis of Mechanisms of Mandible Fractures - Tsutsumi, Yasuhiko; Ito, Daisuke; Nakamura, Mami; Koshinuma, Shinya; Yamamoto, Gaku; Hitosugi, Masahito (Journal of oral and maxillofacial surgery, 2021)
The investigators characterized the occurrence of maxillofacial injuries in cyclists and biomechanically analyzed the mechanisms of mandible fractures. We retrospectively analyzed injury data and performed biomechanical analyses with finite element models. Hospital records from 2011 through 2019 were reviewed to identify patients who had sustained oral and maxillofacial injuries while riding a bicycle. Patients with maxillofacial fractures were compared to those without. Logistic regression analysis was performed to identify which variables were independently associated with the occurrence of maxillofacial fractures. To reconstruct the injury scenario (one in which a person falls from a bicycle and contacts the road surface with their face), computer simulations using The Total Human Model for Safety model were performed. The hospital records of 94 patients (62 men, 32 women; 26.1 ± 17.3 years of age) who sustained oral and maxillofacial injuries while riding a bicycle were reviewed. Twenty patients (21.3%) sustained maxillofacial fractures; mandible fractures were most common (16 patients). Patients with maxillofacial fractures were significantly older and had higher severity injuries; however, logistic regression analysis showed that only age was an independent predictor of the occurrence of maxillofacial fracture (odds ratio, 1.03; P = .025). In simulations, higher von Mises stresses were found in the mandible when the cyclist fell with the neck extended and the body horizontal, and consequently, the center of mandibular body strikes the road surface. Contact forces were approximately 8 kN. High tensile stresses occurred laterally and high compressive stresses occurred medially in the mandibular ramus, which indicated that the mandibular ramus deformed in the transverse plane. Biomechanical analyses show that mandible fractures can occur when a cyclist falls from a bicycle and their lower face strikes the road's surface.